PROBLEM BASED LEARNING DAN KETERAMPILAN BERPIKIR KRITIS - Tyass Bella Pratiwi; Abdul Hakim; Zulkarnaen Zulkarnaen (Vidya Karya, 2020)
Abstract. This research was conducted to improve critical thinking skills students through the application of the Project Based Learning (PBL) model on the material of simple harmonic motion. The research design was a quasi-experimental study with a control group pretest posttest design. The research was conducted at a high school in Samarinda with the number of research subjects consisting of 34 students. The instruments of the research were in the form of an integrated test description with skills critical thinking and a questionnaire of the student responses to the application of the PBL model. The result of the research showed that the of the PBL model (experimental class) improved students' critical thinking skills with N-Gain means of 0.61, while the conventional model (control class) improved students' critical thinking skills with N-Gain means of 0.38. There is a significant difference in critical thinking skills between classes using the PBL model compared to those applying the conventional model on the topic of simple harmonic motion.Keywords: problem based learning, critical thinking, simple harmonic motion.Abstrak. Penelitian ini dilakukan untuk meningkatkan keterampilan berpikir kritis siswa melalui penerapan model Project Based Learning (PBL) pada materi gerak harmonik sederhana. Desain penelitian ini adalah kuasi eksperimen dengan control group pretest posttest design. Penelitian dilakukan pada salah satu SMA di Samarinda dengan jumlah subjek penelitian terdiri dari 34 siswa orang siswa. Instrumen penelitian berupa tes uraian yang terintegrasi dengan keterampilan berpikir kritis dan angket tanggapan siswa terhadap penerapan model PBL. Hasil penelitian menunjukkan bahwa penerapan model PBL (kelas eksperimen) meningkatkan keterampilan berpikir kritis siswa dengan rerata N-Gain sebesar 0,61, sedangkan untuk model konvensional (kelas control) meningkatkan keterampilan berpikir kritis siswa dengan rerata N-Gain sebesar 0,38. Terdapat perbedaan kterampilan berpikir kritis yang signifikan antara kelas dengan menerapkan model PBL dibandingkan dengan yang menerapkan model konvensional pada topik gerak harmonik sederhana.Kata kunci: problem based learning, berpikir kritis, gerak harmonik sederhana.